2020
DOI: 10.5194/angeo-38-35-2020
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation of Pc3–Pc5 geomagnetic pulsation amplitude across the dip equator in central South America

Abstract: In order to clarify the equatorial electrojet effects on ground magnetic pulsations in central South America, we statistically analyzed the amplitude structure of Pc3 and Pc5 pulsations recorded during days considered quiet to moderately disturbed at multiple equatorial stations nearly aligned along the 10 • magnetic meridian. It was observed that Pc3 amplitudes are attenuated around noon at the dip equator for periods shorter than ∼ 35 s. It is proposed that daytime Pc3s are related to MHD (magnetohydrodynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Recent work investigating the occurrence of PC3 waves at the dawnside terminator has shown evidence of what is termed the “sunrise effect” (Saka & Alperovich, 1993; Silva et al., 2020; Somsikov, 2011; Tanaka et al., 2004; Yagova et al., 2017). While the physical processes underlying the generation of these waves remains poorly understood, it is noteworthy that PC3 waves occur frequently at the dawn side terminator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work investigating the occurrence of PC3 waves at the dawnside terminator has shown evidence of what is termed the “sunrise effect” (Saka & Alperovich, 1993; Silva et al., 2020; Somsikov, 2011; Tanaka et al., 2004; Yagova et al., 2017). While the physical processes underlying the generation of these waves remains poorly understood, it is noteworthy that PC3 waves occur frequently at the dawn side terminator.…”
Section: Discussionmentioning
confidence: 99%
“…However, most observations of the “sunrise effect” have been at mid to low latitudes, where ionospheric currents behave quite differently than at the high latitudes studied herein. One of the proposed generation mechanisms for these waves involves the motion of neutral winds across a thermal conductivity gradient (Silva et al., 2020). It is therefore suggested that further observational study of eclipse related ULF waves include a thermospheric wind measurement in conjunction with ionospheric sounding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work investigating the occurrence of PC3 waves at the dawnside terminator has shown evidence of what is termed the "sunrise effect" (Saka & Alperovich, 1993;Somsikov, 2011;Tanaka et al, 2004;Yagova et al, 2017;Silva et al, 2020). While the physical processes underlying the generation of these waves remains poorly understood, it is noteworthy that PC3 waves occur frequently at the dawn side terminator.…”
Section: Discussionmentioning
confidence: 99%
“…However, most observations of the "sunrise effect" have been at mid to low latitudes, where ionospheric currents behave quite differently than at the high latitudes studied herein. One of the proposed generation mechanisms for these waves involves the motion of neutral winds -11-manuscript submitted to JGR: Space Physics across a thermal conductivity gradient (Silva et al, 2020). It is therefore suggested that further observational study of eclipse related ULF waves include a thermospheric wind measurement in conjunction with ionospheric sounding.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the source and propagation mechanisms of the equatorial and very low latitude pulsations are not fully understood, and they might be related to either upstream waves or mechanisms of pulsations at higher latitudes [Yumoto, 1986;Feng et al, 1995]. Some studies reported an attenuation in the amplitudes of Pc3 pulsation at the dip equator especially for short period Pc3 pulsations [Yumoto et al, 1985;Itonaga and Kitamura, 1993;Roy and Rao, 1998;Takla et al, 2011, Graziela et al, 2020, while other studies reported Pc3 amplitudes enhancement at the dip equator [Sarma and Sastry, 1995;Matsuoka et al, 1997;Saka et al, 2001;Zanandrea et al, 2004]. The dip equator is an imaginary line that roughly passes through the points where a magnetic needle has no dip.…”
Section: Latitudinal Dependence Of Pc3-4 Amplitudesmentioning
confidence: 99%